Integrating Cultural Values in Nationalism Character Education: A Study on Merdeka Curriculum Implementation - Wahyudi, Ilham; Wuryandani, Wuri (Universitas Pendidikan Ganesha, 2024)
The character education of nationalism, as outlined in the Merdeka Curriculum, needs to be implemented from an early age, particularly at the elementary school level. However, many teachers still prioritize cognitive assessments over character education. This study aims to explore, analyze, and describe the activities of culture-based nationalism character education conducted by teachers in the classroom. This research employs a qualitative method with data collection through observation, interviews, and documentation. Data analysis is carried out through three stages: data condensation, data presentation, and conclusion drawing. The results indicate that the activities conducted by teachers to foster culture-based nationalism character include four aspects: first, activities to introduce culture; second, activities to appreciate culture; third, interaction across cultural differences; and fourth, reflection on cultural experiences. Can be concluded that the culture-based nationalism character education within the Merdeka Curriculum can thrive through classroom learning, with teachers acting as facilitators who integrate cultural diversity and local wisdom from their respective regions.